22nd May: Trinity Sunday - Duffield, Ian K. (The expository times, 2016)
The article discusses the celebration of Trinity Sunday in the Church year. It states significance of Trinity Sunday in taking people toward doctrines, and mentions the misunderstanding of considering the Bible as a theological textbook. It notes prominence of the names the Father, the Son, and the Holy Spirit in the New Testament.